Analysis of speech development and auditory performance in children after cochlear implantation - Radhakrishnan KR,; Sivasubramanian T,; Rajkamal Pandian D,; Amuthan KR, (Asian Journal of Medical Sciences, 2023)
Background: Hearing loss is a frequent congenital condition. If not treated promptly, the disease’s progression may endanger newborns and young children’s proper growth and development. Cochlear implants (CIs) are the only viable treatment for severe or extremely severe sensorineural hearing loss. Aims and Objectives: This study aimed to see how auditory performance and speech development changed after cochlear implantation in children born deaf and whether there is a link between sociodemographic parameters and the outcome. Materials and Methods: Analyze the improvement of speech and auditory performance in congenitally deaf children aged 1–6 years who underwent CI surgery at Government Rajaji Hospital, Madurai Medical College, Madurai, from January 2016 to June 2018. The data acquired in this study were statistically analyzed to provide detailed findings. Results: Among the study population with age distribution, 18 (26.87%) were in 3 years, followed by 17 (25.37%) in 4 years and least 1 (1.49%) were in 1 year. Sex distribution – 42 (62.69%) were male, and 25 (37.31%) were female children. Progress in hearing and speech was observed, which was evident from the 2-year assessment of categories of auditory performance (CAP) (2.7–4.4) and speech intelligibility rating (SIR) scores (1.04–3.67), increasing every 3 months (P<0.001). Scores of children in age group 2 (CAP2 and SIR 3.3) were the highest, yet differed significantly among age groups, implying that the earlier the CI implantation age, the better their language outcomes were. Conclusion: The importance of age at implantation and the role of family members in effective audioverbal therapy and aural stimulation at home were highlighted in this study.